Current and emerging treatment options in triple-negative breast cancer - Omer Dizdar; Kadri Altundag (Frontiers Media S.A., 2011)
Triple-negative breast cancer is defined by the lack of estrogen receptor, progesterone receptor and HER2 expression with immunohistochemical analysis. Triplenegative breast cancers are poorly differentiated, characterized by high histological grade and occur at a younger age. Treatment options are limited as these tumors are naturally resistant to existing targeted therapies, i.e., endocrine treatment and trastuzumab. An improved understanding of the biology of TNBC has led to evaluation of DNA-damaging chemotherapy drugs and targeted agents, including poly (ADP-ribose) polymerase inhibitors, epidermal growth factor receptor inhibitors, angiogenesis inhibitors, etc., in the treatment of TNBC. This review focuses on outlining the current and emerging treatment options in patients with triple-negative breast cancer.